5‐Fluorouracil‐treated planarians, a versatile model system for studying stem cell heterogeneity and tissue aging. (21st July 2020) - Gambino, Gaetana; Ippolito, Chiara; Modeo, Letizia; Salvetti, Alessandra; Rossi, Leonardo
Abstract : Background Information: Planarians are a sound, well‐established model system for molecular studies in the field of stem cells, cell differentiation, developmental biology and translational research. Treated stem cell‐less planarians produced by X‐ray treatment are commonly used to study stem cell transcriptional profile and their role in planarian biological processes. X‐ray induces oxidative and DNA damage to differentiated cells, requires expensive radiation machines that are not available in most of the research centres and demand rigorous risk management and dedicated staff. Results: We tested the use of the well‐known antimetabolite genotoxic drug 5‐fluorouracil which mainly affects proliferating cells in way to demonstrate its use in replacing X‐ray treatment. We succeeded in demonstrating ability of high doses of 5‐fluorouracil to deplete Dugesia japonica stem cells and in identifying a 5‐fluorouracil transiently resistant population of lineage committed stem cells. Conclusions and Significance: Our results encourage the use of 5‐fluorouracil‐treated planarians as a model system for studying mechanisms of resistance to genotoxicants, planarian stem cell heterogeneity and molecular cascades of tissue aging. Abstract : Research article : We provide a further potentiation of the well‐established model system planarians. Specifically, we demonstrated the ability of 5‐fluorouracil (5FU) to produce stem cell‐less organisms and identified a sub‐population of 5FU transiently resistant stem cells (TRSC), giving insight into the complex heterogeneity of planarian neoblasts. In conclusion, we propose 5FU‐treated planarians as a valid alternative to X‐ray to study stem cell heterogeneity and tissue aging.